Bio-Power Generation in Microbial Fuel Cell with Vermicompost Using Eisenia foetida - Adriana Solares Basurto; Mateo Pérez Ruiz; María Angélica Luján Vega; Juan Manuel Olivares-Ramírez; Irma Lucía Vera-Estrada; José Eli Eduardo González-Duran; Juvenal Rodríguez Reséndiz (Eng)
This research emphasizes the effect of using Eisenia foetida in vermicompost for power generation in microbial fuel cells (MFCs). By accelerating the organic decomposition, the bioenergy generation is improved. A vermicompost-microbial fuel cell employing electrogenic microorganisms was used to convert chemical energy into electrical energy. In this work, substrates of black soil, tree bark, leaves, eggshells, and ground tomatoes were used. The vermicompost MFC has a copper cathode and a stainless steel anode. In this study, the performance of MFCs was evaluated using different numbers of Eisenia foetida specimens, with three specimens (MFCW3), five specimens (MFCW5), and seven specimens (MFCW7). Our key findings show that by increasing the number of Eisenia foetida specimens does not bring higher power densities; as a result, the best power density was observed in MFCW3 and MFCW5 at the end of the fourth week, both presenting a total of five Eisenia foetida specimens with a power density of 192 mW m−2. Therefore, optimal results were found when 330 g of substrate and five Eisenia foetida specimens were used to achieve a maximum current density of 900 mW m−2 and a maximum power density of 192 mW m−2. This type of microbial fuel cell can be considered as an alternative for power generation with a significantly reduced environmental impact, considering the use of organic waste. It can be considered a game-changer in waste management and bioenergy projects.